Minimum Detectable Mass and Volume Fluxes During Magmatic Recharge at High Prominence Volcanoes: An Application to Erciyes Dağ Volcano (Turkey) - Males, Katie; Gottsmann, Jo (Frontiers in Earth Science, 2021)
Magma reservoir recharge triggers changes in the gravitational potential field and can induce volcano deformation. However, the link between magma rejuvenation, ground displacements and gravity changes at volcanoes with a protracted period of quiescence and absence of monitoring data is poorly understood, especially at intra-plate volcanoes where crustal heterogeneity combined with high-prominence are expected to fundamentally affect the crustal stress and strain relationship. Here we report results from integrated geodetic modelling of ground displacements and potential field changes at Erciyes Dağ, a large prominence ($\sim$2800 m) active stratovolcano of the Central Anatolian Volcanic Province in Turkey. With the most recent eruption at $\sim$7000 BC there is a clear need to constrain pre-eruptive subsurface processes and monitoring observables. Developing a suite of numerical models using finite element analysis (FEA) we systematically explore the influence of subsurface mechanical heterogeneities and topography on surface deformation and gravity changes from magmatic recharge of Erciyes Dağ's reservoir. Whilst crustal heterogeneity amplifies deformation and gravity variations, we find that the substantial prominence has the opposite effect. We deduce reservoir volume and mass changes of order 10$^{-3}$ km$^{3}$ and 10$^{10}$ kg, respectively, at the detectability limit of conventional surveying techniques at the volcano. Though dependent on model assumptions, all results indicate that magma recharge at Erciyes Dağ may go undetected at fluxes i) sufficient to maintain an active reservoir containing eruptable magma and ii) similar to those at Parinacota and Mt. Etna. Our findings may be utilised to inform integrated geodetic and gravimetric monitoring at Erciyes Dağ and other large prominence volcanoes and could provide early insights into reservoir rejuvenation with implications for the development of disaster risk reduction initiatives.